Personalized action plans for patients with multiple chronic diseases in Andalusia. (13th November 2019) - Carriazo, A M; Cosano, I; Lama, C; Bedoya, J J; Ollero, M; Lafuente, N; Rodriguez, S; Rodriguez-Acuña, R
Abstract: Issue/problem: Complex chronic patients (CCPs) present multiple chronic conditions and complex healthcare needs. Comprehensive care by multiple healthcare professionals at different settings is required to improve their outcomes. This challenge is faced by the Andalusian Public Health System (APHS), responsible for the provision of healthcare and public health services to the entire Andalusian population (8.5 million inhabitants). Description of the problem: Almost 250000 CCPs have been identified within the APHS in 2018. The very complex ones (4%) utilise up to 30% of primary care and hospital resources. The Comprehensive Healthcare Plan for Patients with Chronic Diseases was launched in 2012 to ensure the comprehensive care for these patients with a multidisciplinary response. Together with the Integrated Care Process Healthcare for Multimorbidity Patients, set the scene for implementing integrated healthcare with coordination of professional services and/or centres over time, helping to decrease clinical variability and improve quality of care. Results: Since 2016, Personalized Action Plans (PAPs) were introduced as key-elements to provide a holistic care coordinated at primary healthcare, including: taking patient's individual needs, preferences and own resources as a starting point for their evaluation and the development their PAPs, involving of patient's informal caregivers, involving all relevant care levels and health disciplines, ensuring the multidisciplinary care with a coordinating team. Lessons: PAPs are a key element in the healthcare process for CCPs, and the assessment of its implementation in Andalusia is contributing to generate evidence within the Joint Action on Chronic Diseases (CHRODIS+, www.chrodis.eu ). Key messages: PAPs implementation and assessment are crucial to better address CCPs health needs, facilitating a patient-centred healthcare approach, and contributing to a European model of care. Involving patient, family carers together with the professional team facilitates achieving better healthcare outcomes.